Public Awareness and Perception of TEVET Activities in Malawi - Manda, Levi Zeleza (Journal of Technical Education and Training, 2017)
This study assessed the impact of Information, Education, Communication and Marketing (IECM) strategy by Malawiâ€™s Technical, Entrepreneurial and Vocational Education and Training Authority (TEVETA) on potential clientsâ€™ awareness of the organisationâ€™s existence understanding of policies on and HIV/AIDS and Gender, and their perception of the importance of  TEVET activities in Malawi. A structured questionnaire was deployed to gather data from a sample of 585 interviewees recruited using a two step sampling design. The findings suggest that the IECM activities were not successful in creating awareness of TEVETA Malawiâ€™s presence and TEVET amongst urban, peri-urban and rural Malawians. Further, the study found that potential client knowledge of what TEVETA does and its policies relating to gender and HIV/AIDS inclusiveness was limited.  For TEVET to become popular and help in driving national economic growth, the study recommends that TEVETA Malawi should espouse  a targeted integrated public communication strategy comprising use of multiple communication channels, strategic placement IECM materials and use of multiple languages.